PENINGKATAN KAPASITAS PENGAWAS TPS PADA PEMILIHAN KEPALA DAERAH PROVINSI KALIMANTAN TENGAH TAHUN 2020 (Jurnal Huma Betang Demokrasi, 2021)
Simultaneous Regional Head Elections in 2020 are the toughest contestations in the history of Regional Head Elections in Indonesia. The 2019 Corona Virus Disease (Covid-19) pandemic situation and the obligation to implement the Health Protocol (Prokes) which limits the interaction space of the community, candidates, political parties carrying, organizers and supervisors in implementation at almost all stages have become an anomaly condition for the realization of the principles of democracy and participation. For the Regional Election Supervisory Board, the COVID-19 pandemic situation is a challenge in increasing the monitoring capacity and quality of implementation. Restrictions on access to direct contact should not limit efforts to realize the participatory and democratic 2020 Simultaneous Pilkada. For this reason, increasing the capacity of TPS supervisors is an important choice. Bawaslu of Central Kalimantan Province based on the results of field research in the Election of Regional Heads of Governor and Deputy Governor of Central Kalimantan Province for the period 2021-2024 in 2020 has made efforts to increase the capacity of TPS supervisors through activities, namely: (i) Technical Guidance, (ii) Providing consultation forum; (iii) Organizing education and training, as well as facilitation. Bawaslu of Central Kalimantan Province is also trying to maximize the performance of ad Hoc supervisors (TPS Supervisors), carrying out consolidation with lower ranks in order to strengthen capacity.